Processing of ethanol-containing waste of oil neutralization in the technology of hand cleaning paste - Petik, Ihor; Belinska , Anna; Kunitsia, Ekaterina; Bochkarev, Sergiy; Ovsiannikova, Tetiana; Kalyna, Viktoriia; Chernukha, Anton; Ostapov, Kostiantyn; Grigorenko, Natalia; Petukhova, Olena (Eastern-European Journal of Enterprise Technologies, 2021)
The graphical dependence of the washing capacity of ethanol-containing soapstock on the concentration in an aqueous solution and the temperature of interaction with the polluted material has been determined. It is proposed to use a 40 % aqueous solution of ethanol-containing soapstock in the hand cleaning paste technology. This soapstock solution has a washing capacity of 92–98 % at the temperature of interaction with the polluted material of 25–40 °C. The regularity of the effect of the structurant content on the consistency of hand cleaning paste was investigated using an approximating polynomial. This made it possible to substantiate the effective concentration of carboxymethyl cellulose (0.4...0.6 %) and cetysltearyl alcohol (1.8...2.0 %) in the formulation. The obtained regression equation is useful for adjusting the content of structurants in the formulation, depending on the consumer’s requirements for the viscosity of the developed detergent. A comparison of the quality indicators of the developed hand cleaning paste based on ethanol-containing soapstock with a sample of similar “Primaterra Automotive” commercial hand cleaning paste was carried out. The quality indicators of the developed paste are as follows: effective viscosity at 20...22 °С – 32.0 Pa∙s; foaming capacity – 23 mm, foam stability – 62.0 %; washing ability – 92.0 %. It was determined that these quality indicators do not differ significantly in the developed detergent and commercial analogue. The data obtained indicate the prospects of processing ethanol-containing soapstock into the hand cleaning paste based on natural surfactants. The developed detergent due to the content of ethanol, glycerin and hydrogen peroxide has antiseptic properties, which is a competitive advantage among analogues. Such utilization of ethanol-containing soapstock makes the process of oil neutralization environmentally safe and economically viable